Strategische Reserve zur Absicherung des Strommarkts - Karsten Neuhoff; Jochen Diekmann; Wolf-Peter Schill; Sebastian Schwenen (DIW Wochenbericht, 2013)
Derzeit wird diskutiert, ob der deutsche Strommarkt genügend Anreize für Investitionen in Kraftwerke und deren Verbleiben am Netz bietet, um die Versorgungssicherheit zu gewährleisten. Vorschläge, die Energieversorgung weiter abzusichern, beinhalten zum Teil umfassende Zahlungen an die Kraftwerksbetreiber - parallel zu Energieerlösen und basierend auf deren Erzeugungskapazität (Kapazitätsmärkte). Andere Vorschläge empfehlen die Vorhaltung einzelner Kraftwerke, die nur bei Knappheit und hohen Preisen zum Einsatz kommen (Strategische Reserve). In der vorliegenden Studie werden die verschiedenen Gründe, die zu fehlenden Investitionsanreizen führen könnten, analysiert und Handlungsoptionen diskutiert. Die Untersuchung zeigt, dass eine Strategische Reserve zur Absicherung der Energieversorgung ausreicht. – – There is an ongoing discussion about whether the German electricity market offers sufficient incentives for investment in power plants and for keeping them connected to the grid, thus ensuring sufficient security of supply. Recommendations for further securing power supply include payments, some of them comprehensive, to power plant operators - in addition to energy revenues and based on their generating capacity (capacity mechanisms). Other suggestions are to keep individual power plants available that are used only during times of scarcity and high prices (strategic reserve). The present article analyzes the various reasons that could lead to a lack of incentives for investment and the extent to which they legitimize employing capacity mechanisms or require other approaches. It is concluded that a strategic reserve would suffice for securing generation adequacy, and finally, design options are discussed.
Keywords: D47; L51; Q48; 330; capacity mechanism; missing money; strategic reserve; Germany; renewable energy